2013
DOI: 10.1371/journal.pone.0069142
|View full text |Cite
|
Sign up to set email alerts
|

Gene Network Analysis of Candidate Loci for Human Anorectal Malformations

Abstract: Anorectal malformations (ARMs) are birth defects that require surgery and carry significant chronic morbidity. Our earlier genome-wide copy number variation (CNV) study had provided a wealth of candidate loci. To find out whether these candidate loci are related to important developmental pathways, we have performed an extensive literature search coupled with the currently available bioinformatics tools. This has allowed us to assign both genic and non-genic CNVs to interrelated pathways known to govern the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The data seem to implicate a large number of different genes and loci, each with only limited support from other sources. Wong et al () also found 12 CNVs larger than 1 Mb in ostensibly isolated patients with ARM, including patients who were diagnosed with autism or who had CNVs that had previously been reported in patients with clear syndromic features. These CNVs had not been associated with ARM previously.…”
Section: Genetic Factorsmentioning
confidence: 86%
See 2 more Smart Citations
“…The data seem to implicate a large number of different genes and loci, each with only limited support from other sources. Wong et al () also found 12 CNVs larger than 1 Mb in ostensibly isolated patients with ARM, including patients who were diagnosed with autism or who had CNVs that had previously been reported in patients with clear syndromic features. These CNVs had not been associated with ARM previously.…”
Section: Genetic Factorsmentioning
confidence: 86%
“…Few studies have been conducted using hypothesis‐generating methods to identify disease‐causing variants for ARM, such as genome‐wide association studies (GWAS). To date, only one small GWAS was performed in 175 patients with ARM, which did not reveal any common SNPs associated with ARM (Wong et al, ). However, a few recent genome‐wide CNV analyses provided potential candidate regions.…”
Section: Genetic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain types of ARM such as recto-perineal fistula and recto-vestibular fistula are also more common to run in families when compared to more complex malformations 27 . Recently a genome-wide copy number variation study indicates that ARM are genetically a heterogeneous disease but this study did not include cloaca anomalies 28 .…”
Section: Cloaca Malformation: the Most Complex And Severe Form Of Anomentioning
confidence: 99%
“…An anteriorly displaced anus is an ARM, which is a relatively frequent defect of hindgut development with an estimated incidence of 1 in 5,000 live births [Wang et al, 2015] and a heterogeneous aetiology with a contribution of both genetic and environmental factors. Chromosome imbalances are found in 4.5-11% of the ARM patients, and anomalies in 17 different chromosomes have been associated with ARM [Marcelis et al, 2011;Wong et al, 2013]. However, none of the reported individuals with a deletion overlapping the region deleted in our patient has this defect.…”
Section: Discussionmentioning
confidence: 54%